(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
This paper aims to explore the way the management control systems(MCSs) work in the Greek banking sector. It also gives us a comparison betweenwhat is currently known and what the findings of the research indicated. Methods The method used for this case study research is described in the book Case study research, Design and Methods (Yin Rober K.,2014). Research questions:Major FindingsThe major findings of this case study research are indicating the way banks exercising their management control. The findings are giving us a clue of how the MCSs are working in the bank from the bottom to the top management level. They are a combination of banks papers research, interviews and in the field observations.